Advances in molecular simulations of protein mechanical properties and function - Franz, Florian; Daday, Csaba; Gräter, Frauke (Current opinion in structural biology, 2020)
Single-molecule force spectroscopy and classical molecular dynamics are natural allies. Recent advances in both experiments and simulations have increasingly facilitated a direct comparison of SMFS and MD data, most importantly by closing the gap between time scales, which has been traditionally at least 5 orders of magnitudes wide. In this review, we will explore these advances chiefly on the computational side. We focus on protein dynamics under force and highlight recent studies that showcase how lower loading rates and more statistics help to better interpret previous experiments and to also motivate new ones. At the same time, steadily increasing system sizes are used to mimic more closely the mechanical environment in the biological context. We showcase some of these advances on atomistic and coarse-grained scale, from asymmetric membrane tension to larger (multidomain/multimeric) protein assemblies under force.
Gesehen am 02.12.2020